Lads : a guide to respect and consent - Bassett, Alan; Wren & Rook (London : Wren & Rook, 2023)
This is a book about how to be the guy that everyone needs right now. Have you ever been in a situation where there's a loud guy making dodgy comments, cracking jokes that only he thinks are funny or leering at the girls in the room? You can feel the tension, right? That guy is the worst, but no one is saying anything, because the whole situation is intimidating and awkward. This toolkit will help you call out bad behaviour and understand the serious issues facing girls today. And it will make you feel confident navigating relationships, so that everyone feels happy, heard and respected, while being the best version of yourself. From flirting disasters and what staying in the friend zone really means, to the perils of porn, "locker room talk" and the importance of consent, this is a vital handbook for lads who are fed up of that guy, and who want to help create positive change.
"This book has been reviewed by an expert who runs gender equality training with young men, and an educational psychologist."
"Recommended for ages 13 and over."
Keywords: seksologia; nuoret aikuiset; käyttäytyminen; ongelmakäyttäytyminen; pojat (ikäryhmät); tasa-arvo; sosiaalinen elämä; seksuaalinen käyttäytyminen; romanssit (ihmissuhteet); pornografia; ongelmat; sexologi; unga vuxna; beteende; problembeteende; pojkar; jämställdhet; socialt liv; sexuellt beteende; romanser (relationer); pornografi; problem; oppaat (teokset); käytösoppaat; nuortenkirjallisuus; englanninkielinen kirjallisuus; guider (verk); etiketthandböcker; ungdomslitteratur